2012
DOI: 10.1097/brs.0b013e318246a53a
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection in Spinal Surgery

Abstract: Used individually, diagnosis-related group, current procedural terminology, and ICD-9 codes cannot completely capture a patient population. Using an algorithm combining all 3 coding systems to generate both inclusion and exclusion criteria, we were able to analyze a specific population of spinal surgery patients within a high-volume medical center. Within that group, risk factors found to increase infection rates were isolated and can serve to focus hospital-wide efforts to decrease surgery-related morbidity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…STB often involves adjacent vertebras and the intervening disc, while leaping and remote lesion is not common and does not characterize the disease. Reviewing the literature, NSTB are mostly reported as episodic case reports in the mainstream academic journals [3], [16], [18]. The incidence of NSTB is reported as 1.1% to 71.4% [2][4], [16], and it is 4.3% in our study.…”
Section: Discussionsupporting
confidence: 51%
“…STB often involves adjacent vertebras and the intervening disc, while leaping and remote lesion is not common and does not characterize the disease. Reviewing the literature, NSTB are mostly reported as episodic case reports in the mainstream academic journals [3], [16], [18]. The incidence of NSTB is reported as 1.1% to 71.4% [2][4], [16], and it is 4.3% in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Previous publications reported that operations of the lumbar and sacral spine were risk factors for SSI; however we could not achieve statistical significance for these attributes. 4, 21-23 An increase in the number of spinal levels involved in a procedure can be linked to a longer operative time, however only the latter was found to be a significant risk factor. Despite a lack of statistical significance, SSI cases were found to have a mean estimated blood loss (EBL) of 400 cc more than non-SSI cases.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors that predispose patients to a SSI have already been analyzed at other institutions; however we determined the risk factors specific to the patient demographics at our institution. 3, 4, 8, 17-20 In addition to risk factor analysis, a thorough investigation of bacteriology changes before and after our intervention was conducted to further study the efficacy of this new prophylactic protocol and to develop strategies for future measures. With the use of several patient databases and extensive chart review, we were able to accurately determine SSI rates at our institution, review risk factors that predispose to SSI specific to our patient demographics, assess bacteriology changes, and ultimately develop a protocol to reduce SSI rates of orthopaedic spine surgeries at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Although longer operative times were dictated mostly by the surgical complexity of the procedure, they can be mitigated by factors such as the proficiency of the surgeon and the operation methods [32]. The proper methods, which can minimize tissue necrosis and decrease infection rates, include releasing the tension on self-retractors often [49] and frequent irrigation of the Number of spinal levels operated 229 [1,50] 3 9 [ 28,35] Surgery involving the sacrum or pelvis 297 [1,33] Larger intraoperative blood loss 216 [26,42] 3 1 [ 12,61] Surgery with spinal instrumentation 856 [33,56] 127 [12,24,27,28,58] Previous surgery 52 [10,50] Blood transfusions 752 [56] 6 1 [ 52] ASA classification 856 [33,56] Limited evidence Hypertension 63 [13] Invasiveness index 63 [13] Renal disease 63 [13] Bony or connective tissue neoplasm 193 [1] Skin to lamina distance 24 [35] Thickness of subcutaneous fat 24 [35] Surgical case order Presence of comorbidities 139 [8,26] Preoperative irradiation 8 [14] Exposure to razor shaving 104 [33] Intraoperative administration of a F i O 2 less than 50 % 104 [33] Suboptimal timing of prophylactic antibiotic therapy 56 [40] Pre-/post-operative elevated serum glucose level 56 [40] 6 …”
Section: Discussionmentioning
confidence: 99%